2007
DOI: 10.1145/1321211.1321258
|View full text |Cite
|
Sign up to set email alerts
|

Information "bridging" in a global organization

Abstract: This paper describes an interview study investigating the collaborative information-seeking andsharing practices of a global software testing team. A site located in Europe was used as a temporal bridge to help in managing time zone differences between the US, China and India. All sites utilized this bridge for critical, synchronous information seeking. Interviews suggest that bridging can be a taxing job and that the success of the bridging arrangement depended upon an intricate balance of temporal, infrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In global distributed software engineering environments, for instance, one crucial aspect of problem solving is information seeking which compromises strategies, e.g. information bridging, Milewski et al, 2007), cognitive processes and behaviors associated with actively acquiring the information required to accomplish some task (Marchionini, 1995;Pirolli and Card, 1999). Information seeking routines can span from formal search, e.g., library sources, to more informal social contact with peers (Milewski, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In global distributed software engineering environments, for instance, one crucial aspect of problem solving is information seeking which compromises strategies, e.g. information bridging, Milewski et al, 2007), cognitive processes and behaviors associated with actively acquiring the information required to accomplish some task (Marchionini, 1995;Pirolli and Card, 1999). Information seeking routines can span from formal search, e.g., library sources, to more informal social contact with peers (Milewski, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ireland also possessed a temporal overlap in standard business hours with all the project locations. Figure 2, which is adapted from Milewski et al (2007), shows typical working days for each of the five locations, all on the same GMT timeline. It is clear that the opportunities for real-time interactions between some of the locations (e.g.…”
Section: A Bridging Example In Software Engineeringmentioning
confidence: 99%
“…At a broad level of analysis, the establishment of a bridge can have positive effects. Both Milewski et al (2007) and Holmström et al (2006) have studied bridge-type arrangements and found that they can facilitate the success of globally distributed projects. In particular, the establishment of a bridge organization can assist the flow of distant team information that is necessary for development and testing of software.…”
Section: Use a Bridge When There Is A High Need For Real-time Interacmentioning
confidence: 99%
See 1 more Smart Citation
“…They are now leveraging the accumulated expertise in managing work they send offshore [7]. Millewski et al [8] study the case of a team in an Irish subsidiary that gradually takes up an "information bridging" role between members of the team in the US and others in an Indian subsidiary. Both these studies focus on multinational companies.…”
Section: The Irish Bridgementioning
confidence: 99%